Lysimachia gesnerioides, a new synonym of Lysimachia baviensis (Primulaceae) - Tong, Yihua; Xia, Nianhe; Hoang, van Sam; Hu, Chi Ming (Phytotaxa, 2017)
In 2006, Zhang et al. described Lysimachia gesnerioides Y.M. Shui & M.D. Zhang in Zhang et al. (2006: 317), on the basis of several collections from Southeast Yunnan, China and North Vietnam, with Y.M. Shui et al. 40906 (KUN) being designated as the holotype. In the protologue, they stated that this species is morphologically close to L. physaloides C.Y. Wu & C. Chen in Chen & Hu (1979: 28), L. grandifolia Hemsl. in Brown (1895: 107) and L. chapaensis Merrill (1939: 350) in the non-odiferous dry plants, alternate or slightly crowded leaves in the upper parts of stems, short filaments, and sagittate or ovate anthers. From their key to aid in the identification of the four species, L. gesnerioides can be differentiated from those species by glabrous and oblong or ovate-elliptic leaves, corymbose inflorescences, yellow flowers with pedicels 1.7‒2.4 cm long, calyx lobes ca. 10 mm long, and ovate anthers opening by apical pores.